Digital-Based Madrasah Examination Management: A Case Study of MAN 3 Palembang, Indonesia - Susmita, Isna; Widayatsih, Tri; Fitriani, Yessi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to examine how digital-based examination management is planned, implemented, and evaluated in an Islamic secondary education context by focusing on a case study at MAN 3 Palembang, Indonesia. Conceptualizing digital assessment as a managerial process, this research adopts a qualitative case study design. Data were collected through in-depth interviews, observations, and document analysis involving school leaders, examination committee members, teachers, and technical staff. The data were analyzed using thematic analysis to capture managerial patterns across planning, implementation, and evaluation stages. The findings reveal that digital-based examinations at MAN 3 Palembang are institutionally governed practices rather than isolated technological interventions. The planning stage demonstrates strategic integration of digital examinations into the madrasah’s academic management framework through collaborative decision-making, leadership involvement, risk anticipation, and resource preparation. Implementation findings indicate that examination integrity, pedagogical alignment, and student adaptation are maintained through coordinated roles among teachers, examination committees, and technical personnel. The evaluation stage functions as a mechanism for continuous improvement, supporting data-informed decision-making, accountability, and organizational learning. The novelty of this study lies in its managerial focus on digital examination practices within a madrasah context, extending existing research that predominantly emphasizes technological effectiveness or student perceptions. Practically, the study highlights the importance of embedding digital examinations within governance structures, strengthening leadership coordination, and institutionalizing evaluation practices. The study contributing to literature on digital governance in faith-based educational institutions by providing context-sensitive insights into how digital examinations are sustainably managed in Islamic secondary education institutions.